2022
DOI: 10.1186/s13102-022-00513-2
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity induced alterations of gut microbiota in humans: a systematic review

Abstract: Background Gut microbiota is considered to have a great impact on human health and disease. While it is widely recognized that the gut microbiota of healthy individuals differs from those with obesity, inflammatory bowel disease, metabolic syndrome, and other chronic diseases, the alterations of gut microbiota with physical activity are not fully understood. Accordingly, we performed this systematic review to address the question regarding the effects of mild and intense exercise on the gut mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 113 publications
(206 reference statements)
1
34
0
1
Order By: Relevance
“…Exercise may then help to upregulate genera commonly considered to be contributory to health through SCFA (particularly butyrate) production [ 68 , 69 , 70 ]. Regardless, it is important to note that across both healthy and clinical populations, the genera most commonly reported to change in response to exercise training appear to be those significantly involved in SCFA production [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise may then help to upregulate genera commonly considered to be contributory to health through SCFA (particularly butyrate) production [ 68 , 69 , 70 ]. Regardless, it is important to note that across both healthy and clinical populations, the genera most commonly reported to change in response to exercise training appear to be those significantly involved in SCFA production [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, a second systematic review was published, and this included 18 studies in humans, with half of those being cross-sectional in design [ 13 ]. More recent reviews have included cross-sectional studies ( n = 25) [ 14 ], older adults only ( n = 7) [ 15 ] or excluded those with clinical conditions and included cross-sectional studies ( n = 38) [ 16 ]. While the early cross-sectional data have been invaluable for describing potential relationships between exercise and gut microbiota, these studies could not address the large interindividual variability in the composition of the gut microbiome in the same way as longitudinal studies have been able to do since.…”
Section: Introductionmentioning
confidence: 99%
“…All these factors are associated with obesity-induced comorbidities. Many factors can cause an alteration of the gut microbiota profile to impact obesity, including diet [ 128 ], BS [ 109 ], physical activity [ 129 , 130 ], probiotics (e.g., Bifidobacterium and Lacticaseibacillus ) [ 131 , 132 ], prebiotics, and synbiotics (containing both probiotic and prebiotic components).…”
Section: Clinical Management Of Obesitymentioning
confidence: 99%
“…Yet, individual factors are the main determinant of athletic performance. In recent years, with the recognition of the significance of the gut microbiome in modulating metabolism, there has been an increasing interest in the contribution of the gut microbiome to individuality in athletic outcomes [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…in the five days post-marathon compared to pre-marathon [ 16 ]. However, recent reviews indicated that there were no specific microbial taxa, or community composition consistently associated with exercise regimes or athletic performance level [ 4 , 5 , 6 ]. Furthermore, while studies found differences between the microbiotas of athletes and sedentary individuals, the variation between individuals was often greater [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%